MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN LKS PADA MATERI LARUTAN PENYANGGA SISWA KELAS XI IPA 2 SMA NEGERI 12 BANJARMASIN - Rezky Purnama Sari; Leny Leny; Parham Saadi (Universitas Lambung Mangkurat, 2014)
Abstract. Improving Students’ Achievement By Using Guided Inquiry Model By Helping Students’ Worksheets (LKS) At Buffer Solution Material For Students Of XI IPA 2 SMA Negeri 12 Banjarmasin In Academic Year 2012/2013 . A research of buffer solution material has been conducted in XI IPA 2 SMA Negeri 12 Banjarmasin. This research is aimed to find teachers’ and students’ improvement in activities, students’ achievement (cognitive, affective, and psychomotor) and response to the learning by using guided inquiry model by helping students’ worksheets (LKS) at buffer solution material. This research used classroom action research (CAR) design with 2 cycles. Each cycle consists of planning, action, observation, and evaluation phases, as well as analysis and reflection. The subjects were 28 students of XI IPA 2 SMA Negeri 12 Banjarmasin. Data were collected through achievement test, observation, and questionnaires. Data were analyzed by percentage technique and elaborated quantitatively and qualitatively. The results showed that the use of guided inquiry model by helping worksheets (LKS) could improve students’ achievement at buffer solution material from the first to second cycle. Teacher activity increased from 57.75 in first cycle to 62.75 in second cycle. Student activity increased from 49.75 in first cycle to 58.25 in second cycle. Students’ achievement increased from 83.18% in first cycle to 96.13% in second cycle. Students’ affective achievement increased from 38.82 in the first cycle to 40.82 in the second cycle with good category. Students’ psychomotor achievement increased from 12.71 in the first cycle with good category to 15.57 in the second cycle with a very good category. Students responded positively to guided inquiry model by helping worksheets (LKS) at buffer solution material.Keywords: guided inquiry model, buffer solution.